2011
DOI: 10.1136/ard.2010.139774
|View full text |Cite
|
Sign up to set email alerts
|

Impact of concomitant use of DMARDs on the persistence with anti-TNF therapies in patients with rheumatoid arthritis: results from the British Society for Rheumatology Biologics Register

Abstract: ObjectiveTo evaluate the effect of different concomitant disease modifying antirheumatic drugs (DMARDs) on the persistence with antitumour necrosis factor (anti-TNF) therapies in patients with rheumatoid arthritis (RA).MethodThis analysis included 10 396 patients with RA registered with the British Society for Rheumatology Biologics Register, a prospective observational cohort study, who were starting their first anti-TNF therapy and were receiving one of the following DMARD treatments at baseline: no DMARD (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
133
3
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(166 citation statements)
references
References 28 publications
20
133
3
10
Order By: Relevance
“…The recommended dose as monotherapy is 8mg/kg given every 4 weeks. Various national registries have revealed that about one third of the patients worldwide are on biologic monotherapy [80,81]. Perhaps this is the strongest selling point of tocilizumab as to date, it is one of the few biologics given as a monotherapy that have shown superiority against methotrexate in head-to-head studies [44].…”
Section: Expert Opinionmentioning
confidence: 99%
“…The recommended dose as monotherapy is 8mg/kg given every 4 weeks. Various national registries have revealed that about one third of the patients worldwide are on biologic monotherapy [80,81]. Perhaps this is the strongest selling point of tocilizumab as to date, it is one of the few biologics given as a monotherapy that have shown superiority against methotrexate in head-to-head studies [44].…”
Section: Expert Opinionmentioning
confidence: 99%
“…[46][47][48][49][50][51][52][53] TCZ has been found to be superior as monotherapy. 54,55 Achieved a Stable Low Disease Activity-State (DOSERA), also showed that dose reduction in TNF inhibitors is possible in RA.…”
Section: Discussionmentioning
confidence: 99%
“…МТ повышает эффективность ингибиторов ФНОα (ИНФ и АДА) за счет разных механизмов, в том числе в связи с подавлением иммуногенности этих моноклональных ан-тител [46,102]. Наряду с материалами РПКИ, данные от-крытых наблюдательных исследований [103,104] и нацио-нальных регистров [105][106][107][108][109][110][111], а также их метаанализ [112] свидетельствуют о более высокой эффективности комби-нированной терапии МТ и ингибиторами ФНОα по срав-нению с монотерапией этими препаратами.…”
Section: таблицаunclassified